Does the Use of Smaller Amplatz Sheath Size Reduce Complication Rates in Percutaneous Nephrolithotomy? - Karakose, Ayhan; Aydogdu, Ozgu; Atesci, Yusuf Ziya (Urology Journal, 2014)
Purpose: To evaluate the effect of Amplatz sheath size used in percutaneous nephrolithotomy (PCNL) on postoperative outcomes, bleeding and renal impairment rates. Materials and Methods: We retrospectively evaluated the records of 91 patients who had undergone PCNL. We divided the patients into 2 groups according to Amplatz sheath size (22 and 30 French [F]) used in the PCNL procedure. Groups were retrospectively compared in terms of pre- and postoperative hemoglobin and renal function, mean nephrostomy time, mean nephrostomy tube diameter, mean operative time, mean hospitalization time and mean scopy time. Results: Mean operative time, mean preoperative hemoglobin and serum creatinine values were similar in 2 groups. The mean stone diameter of patients in group 1 (22F) and group 2 (30F) were 38.47 ± 11.51 mm and 37.69 ± 12.33 mm, respectively. Pre- and postoperative hemoglobin (Hb) levels were 14.52 ± 1.5 g/dL and 13.51 ± 1.4 g/dL, respectively in group 1. Pre- and postoperative Hb level were 14.23 ± 1.6 g/dL and 10.73 ± 1.7 g/dL, respectively in group 2. There was a significant difference between the two groups in terms of mean scopy time (P = .023), postoperative Hb (P = .027), postoperative creatinine (P = .032), mean nephrostomy duration (P = .019), mean nephrostomy diameter (P = .028) and hospitalization time (P = .034). There was significant difference between the two groups in bleeding requiring blood transfusion (P = .023) and residual stone (P = .035). Conclusion: The smaller the Amplatz sheath used in PCNL, the lower kidney hemorrhage and renal function impairment happens.